Evaluation of bond durability, surface morphology, and remineralization at the adhesive interface with dentin bonding agents modified with silica-doped nanohydroxyapatite - Prasanthi Gonapa; Girija S Sajjan; Arun Bhupathi; Uday K Podugu; Suvarna Sundar; Durgabhavani Gondi; R Tejasree Rathod (Wolters Kluwer Medknow Publications, 2022)
Objectives: To compare and evaluate the bond durability, surface morphology, and remineralization of the adhesive layer with newer adhesive systems modified with novel bioactive nanoparticles. Methodology: Bonding agents evaluated in this study include (a) Conventional dentin bonding agent (CN-DBA) (b) Nanohydroxyapatite (nanoHAP) incorporated dentin bonding agent (NH DBA); (c) Silica doped nanohydroxyapatite (Si nanoHAP) incorporated dentin bonding agent (Si NH DBA). A total of 104 human dentin discs (5 mm × 5 mm × 2 mm) were sectioned. Elemental analysis (Ca/P ratio) and surface morphology of the adhesive layer with different dentin adhesives were evaluated under scanning electron microscopy with energy-dispersive X-ray analysis after speculated storage time of 1 day and 6 months. Microshear bond strength of adhesive restorations with different dentin adhesives was evaluated under universal testing machine and fractographic analysis under scanning electron microscope after speculated storage time of 1 day and 6 months. The results were analyzed using analysis of variance and post hoc analysis. Results: Si-NH-DBA showed highest mean microshear bond strength for both 1 day and 6 months, which was significantly higher compared to conventional nanofilled dentin bonding agent (CN-DBA) and NH-DBA. Si-NH-DBA group showed only 10% reduction in bond strength after 6 months, which was less compared to that of other groups. Similarly, Si-NH-DBA showed higher remineralization with stellate-shaped crystals at the adhesive layer after 6 months with hydrolytic resistant hybrid layer, compared to CN-DBA and NH-DBA. Conclusion: Silica-doped nanohydroxyapatite proved its efficiency on bond stability, remineralization, and hydrolytic resistance when incorporated into dentin bonding agents because of its bioactivity and carbonate-containing apatite-forming ability.